ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN VOLUME PERDAGANGAN TERHADAP RETURN SAHAM (studi kasus pada perusahaan real estate and property yang terdaftar di BEI periode 2007-2010) - Widayanti, Puri; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2013)
The development of stock returns on the real estate and property industry in 2007-2010 fluctuated sharply. This study is conducted to examine the effect of the Debt to Total Asset ratio (DTA), Earning Per Share (EPS) and Trading Volume on the stock returns.Sampling method used in this study was purposive sampling method, which was based on certain criteria. Samples that match with the criteria of this research were 31 real estate and property companies on the Indonesian Stock Exchange in the period 2007-2010. The analysis used was multiple linear regressions, to see whether the independent variables influence the dependent variable.Based on the results of this study, there are no variables that deviate from the classical assumptions. It indicates that the available data has been qualified in order to use the multiple linear regression equation models. Based on the hypothesis test, variable of Debt to Total Asset Ratio (DTA) and the trading volume have partially influenced the effect on the stock returns of the property and real estate companies which are listed in the Indonesian Stock Exchange 2007-2010, while Earning Per Share(EPS) partially has no significant effecton the stock returns. This paper also shows that DTA is the most dominant factor in influencing the Stock Return, as proven by the regression coefficient value of 0.469, which larger compared to other variables. The predictive ability of these three variables on the stock returns are about 27.1%.